Whole-Genome Sequencing of Gram-Negative Bacteria Isolated From Bovine Mastitis and Raw Milk: The First Emergence of Colistin mcr-10 and Fosfomycin fosA5 Resistance Genes in Klebsiella pneumoniae in Middle East - Tartor, Yasmine H.; Abd El-Aziz, Norhan K.; Gharieb, Rasha M. A.; El Damaty, Hend M.; Enany, Shymaa; Soliman, Enas A.; Abdellatif, Samah S.; Attia, Amira S. A.; Bahnass, Mosa M.; El-Shazly, Yousry A.; Elbediwi, Mohammed; Ramadan, Hazem (Frontiers in Microbiology, 2021)
Antimicrobial resistance is a major concern in the dairy industry. This study investigated the prevalence, antimicrobial resistance phenotypes, and genome sequencing of Gram-negative bacteria isolated from clinical (n = 350) and subclinical (n = 95) bovine mastitis, and raw unpasteurized milk (n = 125). Klebsiella pneumoniae, Aeromonas hydrophila, Enterobacter cloacae (100% each), Escherichia coli (87.78%), and Proteus mirabilis (69.7%) were the most prevalent multidrug-resistant (MDR) species. Extensive drug resistance (XDR) phenotype was found in P. mirabilis (30.30%) and E. coli (3.33%) isolates. Ten isolates (four E. coli, three klebsiella, and three P. mirabilis) that displayed the highest multiple antibiotic resistance (MAR) indices (0.54 - 0.83), were exposed to whole-genome sequencing (WGS). Two multilocus sequence types (MLST): ST2165 and ST7624 were identified among the sequenced E. coli isolates. Three E. coli isolates (two from clinical mastitis and one from raw milk) belonging to ST2165 showed a similar profile of plasmid replicon types: IncFIA, IncFIB, IncFII, and IncQ1 with an exception to an isolate that contained IncR, whereas E. coli ST7624 showed a different plasmid profile including IncHI2, IncHI2A, IncI1α, and IncFII replicon types. ResFinder findings revealed the presence of plasmid-mediated colistin mcr-10 and fosfomycin fosA5 resistance genes in a K. pneumoniae (K1) isolate from bovine milk. Sequence analysis of the reconstructed mcr-10 plasmid (pK1) from WGS of isolate K1, showed that mcr-10 gene was bracketed by xerC and insertion sequence IS26 on an IncFIB plasmid. Phylogenetic analysis revealed that isolate K1 existed in a clade including mcr-10-harboring isolates from human and environment with different STs and countries [UK (ST788), Australia (ST323), Malawi (ST2144), Myanmar (ST705), and Laos (ST2355)]. This study reports the first emergence of K. pneumoniae co-harboring mcr-10 and fosA5 genes from bovine milk in Middle East, that constitutes a public health threat and heralds the penetration of the last-resort antibiotics. Hence, prudent use of antibiotics in both humans and animals and antimicrobial surveillance plans are urgently required.